Power Generation and Regional Collaboration in South Asia - Alam, Firoz; Sarkar, Rashid; Alam, Quamrul (Journal of the Institute of Engineering, 2020)
Inadequate power generation and supply are considered to be the main hindrance of economic development and prosperity in South Asia. Limited indigenous energy resource of each South Asian nation is not suitable to generate sufficient power. Moreover, the availability of limited indigenous energy resources differs among South Asian nations. The power demand and power generation capacity notably vary among the countries due to seasonal variability. This paper highlights the need for a collective effort to develop mechanism for the utilisation of limited resources and enhance the cross-border power trade among South Asian nations. Bilateral and multi-lateral cooperation will allow overcoming regional power shortage and augmenting collective energy security.